Mineralization Styles in the Orogenic (Quartz Vein) Gold Deposits of the Eastern Kazakhstan Gold Belt: Implications for Regional Prospecting - Konopelko, Dmitry L.; Zhdanova, Valeriia S.; Stepanov, Sergei Y.; Sidorova, Ekaterina S.; Petrov, Sergei V.; Kozin, Aleksandr K.; Aliyev, Emil S.; Saltanov, Vasiliy A.; Kalinin, Mikhail A.; Korneev, Andrey V.; Seltmann, Reimar (Minerals (Basel), 2025)
The Eastern Kazakhstan Gold Belt is a major black-shale-hosted gold province in Central Asia where the main types of deposits comprise mineralized zones with auriferous sulfides (micro- and nano-inclusions of gold and refractory gold) and quartz veins with visible gold. The quartz vein deposits are economically less important but may potentially represent the upper parts of bigger ore systems concealed at depth. In this work, the mineralogy of the quartz vein deposits and related wall rock alteration zones was studied using microscopy and SEM-EDS analysis, and the geochemical dispersion of the ore elements in primary alteration haloes was documented utilizing spatial distribution maps and statistical treatment methods. The studied auriferous quartz veins are classified as epizonal black-shale-hosted orogenic gold deposits. The veins generally have linear shapes with an average width of ca. 1 m and length up to 150 m and contain high-grade native gold with minor amounts of sulfides. In supergene oxidation zones, the native gold is closely associated with Fe-hydroxide minerals cementing brecciated zones within the veins. The auriferous quartz veins are usually enclosed by the wall rock alteration envelopes, where two types of alteration are distinguished. Proximal phyllic alteration (sericite-albite-pyrite ± chlorite, Fe-Mg-Ca carbonates, arsenopyrite, and pyrrhotite) develops as localized alteration envelopes, and pervasive carbonation accompanied by chlorite ± sericite and albite is the dominant process in the distal alteration zones. The rocks within the alteration zones are enriched in Au and chalcophile elements, and three groups of chemical elements showing significant positive mutual correlation have been identified: (1) an early geochemical assemblage includes V, P, and Co (±Ni), which are the chemical elements characteristic for black shale formations, (2) association of Au, As, and other chalcophile elements is distinctly overprinting, and manifests the main stage of sulfide-hosted Au mineralization, and (3) association of Bi and Hg (±Sb and U) includes the chemical elements that are mobile at low temperatures, and can be explained by activity of the late-stage hydrothermal or supergene fluids. The chalcophile elements show negative slopes from proximal to distal alteration zones and form overlapping positive anomalies on spatial distribution mono-elemental maps. Thus, the geochemical methods can provide useful tools to delineate the ore elemental associations and to outline reproducible anomalies for subsequent regional gold prospecting.